2010
DOI: 10.1021/es903860w
|View full text |Cite
|
Sign up to set email alerts
|

From Individual to Population Level Effects of Toxicants in the Tubicifid Branchiura sowerbyi Using Threshold Effect Models in a Bayesian Framework

Abstract: Effects of zinc were studied in the freshwater worm Branchiura sowerbyi using partial and full life-cycle tests. Only newborn and juveniles were sensitive to zinc, displaying effects on survival, growth, and age at first brood at environmentally relevant concentrations. Threshold effect models were proposed to assess toxic effects on individuals. They were fitted to life-cycle test data using Bayesian inference and adequately described life-history trait data in exposed organisms. The daily asymptotic growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Principles and details of Bayesian statistics can be found in Ntzoufras (2009). Some introductory ecotoxicological applications of Bayesian inference can be found in Billoir et al (2008a), Ducrot et al (2010) and Fox (2010).…”
Section: Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Principles and details of Bayesian statistics can be found in Ntzoufras (2009). Some introductory ecotoxicological applications of Bayesian inference can be found in Billoir et al (2008a), Ducrot et al (2010) and Fox (2010).…”
Section: Conceptmentioning
confidence: 99%
“…The different methods/models were compared on the same battery of nine experimental data sets, where the freshwater invertebrate Daphnia magna was exposed to nine different contaminants. Based on previous works (Billoir et al 2008a;Ducrot et al 2010;Fox 2010), we chose Bayesian inference to estimate model parameters, in particular LC 50 and NEC values and their uncertainty. One of the main advantages of Bayesian inference is the use of prior information (coming from expert knowledge or literature) expressed as probability distributions on parameters, which are combined with data in order to provide posterior distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al (1982) have found that the LC50 for temperature is 35°C, which is very close to the temperature (34°C) used by Mukherjee & Kaviraj (2011) in their acute bioassays with cobalt, which may cause uncertainty as to whether the actual cause of mortality among the organisms is due to temperature, to the chemical or to a combination of both. In chronic bioassays, the most noticeable difference concerns length of exposure, which ranged between 28 (Ducrot et al 2010) and 220 days (Casellato et al 1992), and other variations noted included container size, sediment and water volume, and organism density. In most cases, such methodological discrepancies make the comparison of results impossible.…”
Section: Review Of Bioassay Methodsmentioning
confidence: 99%
“…This was the first long-term toxicity experiment using B. sowerbyi. Ducrot et al (2010) also performed chronic bioassays to assess long-term Zn effects on the partial (28 days) and full (179 days) life-cycles of B. sowerbyi. In order to assess the effects of the metal on the partial life-cycle (PLC), the authors ran five bioassays: one with young organisms (14 days old), one with youngadults (40 days old), two with adults (60 days old) and one with cocoons.…”
Section: Branchiura Sowerbyi As a Test-speciesmentioning
confidence: 99%
“…As a number of reports in our review demonstrate, the same potential effects (of chemicals and other stressors) at the organism level can have vastly different consequences at the population level in different species . For example, certain effects of toxicants for a population can exceed the effects observed in individuals , or may be lower . Potential population‐level effects may also change depending on other factors in the model (e.g., population density ).…”
Section: Limitations Of Current Effects Assessments and Implications mentioning
confidence: 98%